A escritura dramática: a utilização de vídeo game como ferramenta de aprendizagem - Martins, José Carlos Ribeiro (2016)
The present article establishes a reflection demonstrating the paths of a research around the teaching of the theater realized with the objective of structuring a proposal of aesthetic creation, through the use of exercises of dramatic writing realized in the classroom, as part of the process of Development of a video game by the participating students.